Observation of Climacteric-Like Behavior of Citrus Leaves Using Fluorescence Spectroscopy - Caio B. Wetterich; Emery C. Lins; José Belasque; Luis G. Marcassa (Journal of Spectroscopy)
Observation of climacteric-like behavior in citrus leaves depends on the detection of ethylene. However, such detection requires a gas chromatographer and complex sample preparation procedures. In this work, fluorescence spectroscopy was investigated as a diagnostic technique for climacteric-like behavior in citrus leaves. Our results indicate that the chlorophyll fluorescence presents a time evolution consistent with the ethylene evolution. Therefore, fluorescence spectroscopy may be used to observe the climacteric-like behavior in citrus leaves.